The logarithmic coefficients and the successive coefficients of Bazilevič functions of order α + iμ. Issue 11 (1st November 2020) - Niu, Xiaomeng; Tang, Huo; Ma, Lina
ABSTRACT: In this article, we introduce a subclass B ( α, μ, A, B ) of Bazilevič functions of order α + i μ and estimate the logarithmic coefficients and the difference of moduli of successive coefficients for the function belonging to the above class. The results obtained generalize some known results.